2023
DOI: 10.1002/ncp.11039
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐upper arm circumference in hospitalized pediatric patients with cancer: Is there an association with malnutrition?

Abstract: BackgroundMalnutrition is common in children/adolescents with cancer. Mid‐upper arm circumference (MUAC) is recommended by the International Society of Pediatric Oncology for measuring nutrition status. The aim was to evaluate the nutrition status of pediatric patients with cancer and verify whether MUAC is associated with malnutrition and length of stay (LOS).MethodsThis was an observational study of patients aged 0–19 years with solid and hematological neoplasms. Data included anthropometric measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The relationship between AC and nutritional status in elderly individuals has been widely studied [ 11 ]. Low AC has been associated with malnutrition, muscle wasting, and frailty in older adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between AC and nutritional status in elderly individuals has been widely studied [ 11 ]. Low AC has been associated with malnutrition, muscle wasting, and frailty in older adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors emphasize the value of arm anthropometry such as MUAC and TSFT, which are considered sensitive indices independent of tumor mass, in order to avoid the underestimation of malnutrition prevalence. The first recommendations date from the late 1990s [ 44 , 45 , 46 , 47 , 48 ]. Although arm anthropometry, according to abundant published data, assists in undernutrition recognition during pediatric cancer treatment, some studies have failed to present sufficient evidence in favor of its use in survivorship [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that skinfold thickness is associated with the nutritional health status of the human body. [38][39][40] Pedro et al 38 showed that triceps skinfold thickness can be used to assess nutritional status in children and adolescents with cancer and is closely related to body BMI. Wang et al 39 found a positive correlation between TSF thickness and the proportion of insulin resistance emerged and also a positive correlation with BMI by retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Skinfold calipers are commonly used instruments for skinfold thickness measurement 36,37 . Studies have shown that skinfold thickness is associated with the nutritional health status of the human body 38–40 . Pedro et al 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation